A comprehensive ecological management approach for northern mountain rivers in China. (November 2019) - Chen, Qingfeng; Guo, Beibei; Zhao, Changsheng; Zhang, Jing
Abstract: Mountain rivers not only play an important role in flood control, but also perform other functions such as conserving water sources, regulating microclimate, and maintaining water ecology and biodiversity. Because the conventional approach to managing mountain rivers overlooks the intrinsic requirements of river water, alters the natural landscape of river channels, and destroys habitats, it leads to water quality deterioration and ecological imbalance. The Yang River is characteristic of northern mountain rivers, and so the ecological management project for this river – at the site of the forthcoming Beijing 2022 Olympic Winter Games – was selected as an example of comprehensive ecological management. This comprises an ecological, permeable dam–pond–wetland system. Results showed that: (Zhu et al., 2006): river water quality improved substantially; improvements in the water quality indices exhibited the trend suspended solids (SS) > ammonium-nitrogen (NH3 -N) > chemical oxygen demand (COD) (Mikus et al., 2019). The Shannon–Wiener diversity index, Margalef species richness index, and Pielou evenness index all indicated increased phytoplankton by an average of 52.1%, 2.4%, and 98.9%, respectively. These three diversity indices showed increased zooplankton, by an average of 1.2%, 0.5%, and 3.3%, respectively. Water quality in the Yang River was found to have changed from moderate to light pollution (Kuemmerlen et al., 2019). Each subsystem increased removal of pollutants from the Yang River. Removal efficiencies of COD, total phosphorous (TP), total nitrogen (TN), NH3 -N, and SS by the dam system were 28.57%, 28.3%, 20.5%, 24.0%, and 95%, respectively. Corresponding pollutant removal efficiencies by the pond system were 16.7%, 29.58%, 21.63%, 20.0%, and 99.8%, respectively. The wetland system achieved pollutant removal efficiencies of 44.0%, 17.1%, 6.7%, 13.9%, and 80.0%, respectively. This approach can mitigate flood control pressure, restore river ecology, and improve water quality in northern mountain rivers, and allow such rivers to achieve "retention–storage–restoration" effects. The ecological treatment approach provides an important theoretical foundation and technical reference for global mountain river management, and is especially applicable to mountain rivers in cold and arid regions in the northern hemisphere. Highlights: Hydrological characteristics of the northern mountain river. Characteristics of water quality change in the northern mountain river. Characteristics of river biodiversity change before and after construction. Water purification and pollutant removal efficiency of the approach.